2019
DOI: 10.1038/s41598-019-44497-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity associated with time discounting in chronic pain

Abstract: Chronic pain (CP) is a global problem extensively associated with an unhealthy lifestyle. Time discounting (TD), a tendency to assign less value to future gains than to present gains, is an indicator of the unhealthy behaviors. While, recent neuroimaging studies implied overlapping neuro mechanisms underlying CP and TD, little is known about the specific relationship between CP and TD in behavior or neuroscience. As such, we investigated the association of TD with behavioral measures in CP and resting-state br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…The WHO-QOL BREF Physical Health domain assesses someone’s body condition to perform daily living activities, including questions on the dependence on medicinal substances and medical aids, level of energy and fatigue, mobility, pain, and discomfort, sleep and rest and work capacity. Previous studies have reported associations between different facets of physical functioning and lower future valuation, such as chronic pain (Tompkins et al, 2016; Wakaizumi et al, 2019), sleep deprivation (Curtis, Williams, & Anderson, 2018); or greater future valuation, such as physical activity (Tate, Tsai, Landes, Rettiganti, & Lefler, 2015) in different populations. Overall, the significant relationship between delay discounting and physical health with delay discounting rate accounting for 24% of the total effect between psychological score and remission status is consistent with those findings, suggesting that the capacity to perform daily tasks plays an important role in the subjective valuation of the future among individuals in recovery from substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO-QOL BREF Physical Health domain assesses someone’s body condition to perform daily living activities, including questions on the dependence on medicinal substances and medical aids, level of energy and fatigue, mobility, pain, and discomfort, sleep and rest and work capacity. Previous studies have reported associations between different facets of physical functioning and lower future valuation, such as chronic pain (Tompkins et al, 2016; Wakaizumi et al, 2019), sleep deprivation (Curtis, Williams, & Anderson, 2018); or greater future valuation, such as physical activity (Tate, Tsai, Landes, Rettiganti, & Lefler, 2015) in different populations. Overall, the significant relationship between delay discounting and physical health with delay discounting rate accounting for 24% of the total effect between psychological score and remission status is consistent with those findings, suggesting that the capacity to perform daily tasks plays an important role in the subjective valuation of the future among individuals in recovery from substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also present the potential for alterations of the DMN [ 10 , 16 , 41 , 42 , 43 , 44 ], FPN [ 11 , 45 , 46 , 47 ], and SN [ 12 , 48 , 49 ] in those experiencing chronic pain, exposing the necessity to further investigate neurological mechanisms underlying chronic pain. Hypotheses of Aytur and colleagues’ study [ 21 ] were rooted in the theory that hyper-connectivity between these three networks (DMN, FPN, and SN) exists in the brains of individuals with chronic pain [ 12 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple previous studies also present the potential for alterations of the DMN (Napadow et al, 2010; Kornelsen et al, 2013; Kuner & Flor, 2017; Karafin et al, 2019; Wakaizumi et al, 2019; Zhang et al, 2019), FPN (Pfannmöller & Lotze, 2019; Kutch et al, 2017; Zheng et al, 2020; Androulakis et al, 2018), and SN (Hemington et al, 2016; Bishop et al, 2018; Seeley, 2019) in those experiencing chronic pain, exposing the necessity to further investigate neurological mechanisms underlying chronic pain. The hypotheses of Aytur and colleagues’ (2020) study were rooted in the main idea that hyper-connectivity between these three networks (DMN, FPN, and SN) exists in the brains of individuals with chronic pain (Hemington et al, 2016; Napadow et al, 2010; van Ettinger-Veenstra et al, 2019).…”
Section: Discussionmentioning
confidence: 99%